Assessing the post-LASPO effect on legal aid and the number of orders: the case of the Children Act - Kalliris, Konstantinos; Alysandratos, Theodore; Jonuzaj, Mariol (SSRN, 2022)
This article explores the effects of cuts to legal aid on access to justice. The Legal Aid, Sentencing and Punishment of Offenders Act 2012 (LASPO) introduced extensive cuts, including the exclusion of almost the entire area of private family law from its scope. We empirically assess the effects of this reform on access to justice, using formal statistical techniques. We find that the cuts had an adverse impact on the availability of legal aid and, consequently, access to justice. This adverse impact was mostly linked to areas where people need legal aid the most (due to high unemployment and low growth), thus undermining both equal access to justice and, arguably, equality of arms in the courtroom. We also find that the average of cost of legal aid per case is approximately £8,000, and, therefore, some cases could be funded at relatively low cost for the taxpayer. Given the failure of mediation to cover for the lack of access to family courts and the emergence of legal aid deserts, we raise the question whether the blanket removal of almost an entire are of law from LASPO’s scope is a justifiable policy.